1998
DOI: 10.1177/002076409804400401
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Labelling, Sex Role Stereotypes and Beliefs About the Mentally Ill

Abstract: This study aimed to investigate the effect of two main variables on specific attitudes and beliefs about mental illness. The first variable tested the labelling theory proposal that the label of mental illness per se is stigmatizing for those so labelled. The second tested the proposal of Rosenfield (1982) that males and females receive a more severe societal reaction for deviance when the deviant behaviour is inconsistent with traditional sex role norms. Questionnaires with vignettes describing four behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
0
21
1
1
Order By: Relevance
“…Several other authors have revealed the importance of 'bizarre' or otherwise deviant behavior (e.g. Cormack & Furnham, 1998;Kirk, 1974;Phillips, 1964). Leaning on these studies, we expect that clients with more symptoms will report more rejection experiences.…”
Section: Service and Client Level Determinants Of Rejection Experiencesmentioning
confidence: 75%
“…Several other authors have revealed the importance of 'bizarre' or otherwise deviant behavior (e.g. Cormack & Furnham, 1998;Kirk, 1974;Phillips, 1964). Leaning on these studies, we expect that clients with more symptoms will report more rejection experiences.…”
Section: Service and Client Level Determinants Of Rejection Experiencesmentioning
confidence: 75%
“…Most research on the signal step of 129 stigma has examined disorders associated with fear or dangerousness, presenting vignettes of 130 M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 behaviors as schizophrenia or as a mental illness led respondents to view the condition as more 135 serious and the person's social skills as more impaired than when the same symptoms were 136 presented without a disease label (Angermeyer and Matschinger, 1996;Arkar and Eker, 1994; 137 Cormack and Furnham, 1998;Sarbin and Mancuso, 1970; for a review, see Read et al, 2006). 138…”
Section: Introduction 44mentioning
confidence: 99%
“…However, Wirth and Bodenhausen (2009) found the opposite effect: Individuals with gender atypical mental illnesses were evaluated more favorably because the illness was seen as more likely to be a genuine, biologically based mental disturbance (see also Sprock, Crosby, & Nielsen, 2001). In addition, many studies have found that men are treated more harshly for mental illness than women, regardless of the specific type of illness (e.g., Cormack & Furnham, 1998;Phillips, 1964;Schnittker, 2003;Tudor, Tudor, & Gove, 1977).…”
Section: Prejudice Toward People With Multiple Category Membershipsmentioning
confidence: 99%